Remote Sensing of Clouds and the Atmosphere VII 2003
DOI: 10.1117/12.463362
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms leading to NLTE IR emission in the terrestrial thermosphere and their impact on remote sensing of atmospheric parameters

Abstract: Assuming large signal-to-noise ratio and using the rotationally resolved fundamental vibration-rotation band emission from NO near 5.3 µm we propose a scheme for remotely sensing temperature above the altitudes where the 15 µm emission from CO 2 becomes very weak. We also find that the rotationally resolved 5.3 µm emission can be used to remotely sense N( 4 S) atom, O 2 , and O densities in the terrestrial thermosphere -this being the only method for remotely sensing the first two species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“… Duff et al [2003] have since shown that this rate coefficient is given by the expression k(T) = 6.2 × 10 −12 (T/300) cm 3 /(s‐molecule) instead of the nearly temperature independent value 2.8 × 10 −12 exp(185/T) cm 3 /(s‐molecule) given in the literature [ Herron , 1999]. Sharma et al [2002] have in addition reported the vibrational‐rotation distribution of the nascent NO produced by this reaction at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… Duff et al [2003] have since shown that this rate coefficient is given by the expression k(T) = 6.2 × 10 −12 (T/300) cm 3 /(s‐molecule) instead of the nearly temperature independent value 2.8 × 10 −12 exp(185/T) cm 3 /(s‐molecule) given in the literature [ Herron , 1999]. Sharma et al [2002] have in addition reported the vibrational‐rotation distribution of the nascent NO produced by this reaction at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The radiance level as well as the width of the P and R branches of the spectrum is larger than for the quiescent case (Figure 1) indicating a higher rotational temperature. This is because the reaction of N( 4 S) and N( 2 D) atoms with O 2 produce highly rotationally and vibrationally excited NO [ Duff et al , 1994; Sharma et al , 2002] which, after losing the vibrational energy, is still highly rotationally excited. These highly rotationally excited NO molecules have a larger cross section for vibrational excitation upon impacts with O and yield vibrationally excited NO molecules with higher rotational temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation